Society 5.0 Era : A Challenge for Contemporary Islamic Education - Jumari, Jumari; Umam, Khoirul (Journal Of Islamic Education And Pesantren, 2023)
The emergence of the Society 5.0 era, characterized by the integration of artificial intelligence, big data, and cyber-physical systems into human life, presents complex challenges for contemporary Islamic education. Beyond technological adaptation, Islamic education faces epistemological, ethical, and pedagogical demands to remain relevant while preserving its foundational values. This study aims to analyze the challenges posed by Society 5.0 and formulate a conceptual framework for strengthening Islamic education in response to digital transformation. Using a qualitative library research approach with a critical-analytical perspective, this research examines contemporary educational discourse, Islamic pedagogical principles, and the implications of technological disruption on learning systems. The findings indicate that the challenges of Society 5.0 encompass three major dimensions: (1) the shift in knowledge authority from traditional religious transmission to digital information ecosystems, (2) the transformation of learning patterns toward technology-mediated and personalized models, and (3) the risk of moral and spiritual disorientation amid hyper-connectivity. Therefore, Islamic education must undertake epistemological integration between revelation and scientific knowledge, develop adaptive and technology-based pedagogical models, and strengthen character education rooted in tawhid, adab, and ethical responsibility. In this context, Society 5.0 should not be perceived merely as a technological disruption, but as an opportunity to reconstruct Islamic education toward a more human-centered, value-driven, and transformative paradigm.